Pojok Literasi Sekolah Sebagai Wadah Untuk Meningkatkan Kualitas Pendidikan di SDN 065011 Medan - Rosepa Ayu Lumbantobing; Fajar Utama Ritonga (Yayasan Literasi Sains Indonesia, 2023)
MBKM is a self-contained and versatile mode of higher education learning designed to create a non-restrictive creative learning community that meets the needs of students. Where the aim of this program is to assist teachers in implementing face-to-face learning, technology adaptation, and school administration, especially school literacy and numeracy. One of the main programs implemented in the target schools is literacy activities due to the low level of literacy at Sdn 065011 Asam Kumbang Medan. Literacy is the quality or ability to be literate/literate which includes the ability to read and write. So to solve this problem, there are several literacy learning activities or methods that I apply to students, especially in Class 5A, namely the first of course is to create a literacy corner in the class with various types of reading books, then carry out silent reading activities, learn to write an essay as well as fiction and non-fiction stories, storytelling in class, drawing, learning public speaking, and watching movies and learning to listen to every vocabulary. With this program, students' interests and talents in literacy are increasingly visible, where reading and writing are getting better and smoother than before. It is hoped that this literacy activity can continue and be implemented by teachers in every class, that way the literacy level of the Sdn 065011 school will improve and be of better quality.